Identification of Material-Related Risks in Green Buildings - Polat, Gul; Turkoglu, Harun; Gurgun, Asli Pelin (ELSEVIER SCIENCE BV, 2017)
Green projects, especially housing projects, have become popular in recent years in the Turkish construction industry. Although the number of green projects is increasing, this type of projects involves several material-related risks. The contractors, who undertake green projects, should be aware of these risks and take precautions against them in order to shield themselves from the possible negative outcomes of these risks. The aim of this study to identify the material-related risk factors that can be experienced by contractors during the construction phase of these projects. For this purpose, an extensive literature review was carried out and a total of 25 factors were identified and a questionnaire survey was designed. These questionnaires were submitted to 50 randomly selected contractors, designers, and consultants and 25 of them returned the completed questionnaires. Based on the responses, the impacts of these risks on cost and time performances of the green projects were ranked and evaluated. It was found that negligence of constructability in green designs is the most severe risk factor that affects the cost and time performances of green projects, and the most severe factors are design-related and contractor-related factors. (C) 2017 The Authors. Published by Elsevier Ltd.
Keywords: Green projects; sustainability; risk factors; time; cost; developing countries; CONSTRUCTION PROJECTS; Construction & Building Technology; Engineering